PENERAPAN KONSELING RATIONAL EMOTIVE THERAPY (RET) UNTUK MENINGKATKAN PUBLIC SPEAKING SISWA KELAS XI SMA N 1 GEBOG - Ahyani, Devyta; Hidayati, Richma; Kiswantoro, Arista (Universitas Muria Kudus, 2023)
Students' low public speaking skills will hamper cognitive, psychomotor, social developmental tasks as well as learning outcomes because students who have low public speaking skills tend to have difficulty conveying their ideas and information. Inappropriate handling can also cause other negative impacts. Rational Emotive Therapy (RET) counseling is a process of assistance by the counselor to the counselee in overcoming problems caused by irrational ways of thinking. This case study research was carried out in class XI SMAN 1 Gebog with 2 research subjects and 3 counseling sessions. Data collection techniques used are observation, interviews and documentation. The results of this study identify the factors that cause low counselee public speaking skills, namely anxiety that starts with irrational thoughts. After implementing RET counseling three times, SNA and ABP experienced a more positive change in attitude and thinking so they were able to improve their public speaking skills.